‘Women’s Work’ in Indonesia’s Social Media-based Online Store Business: Social Reproduction and the Feminization of Work - Fathimah Fildzah Izzati (Journal of Indonesian Social Sciences and Humanities, 2020)
This paper seeks to analyze ‘women’s work’ in Indonesia’s online shop businesses by looking at the forms of work that emerge in those businesses. This paper employs qualitative research methods by using transcribed in-depth interviews with 20 informants from six cities in Indonesia. By looking at flexibility as the defining characteristic of exploitation under platform capitalism, home as the central working space in the social media-based online store, and the ongoing process of feminization of work in the online business sector, this study advances two claims. First, the intersection between platform capitalism and logistics revolution in the online shop business has created new forms of work. Second, the social media-based online store, which is mostly operated by women, shows that flexibility and feminization of work under platform capitalism have direct impacts on the lives of the female business operators and their work. A closer look at the emergence of online stores also reveals how social reproduction work shapes ‘women’s work’ in the online business